Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure! Let's solve the quadratic equation given:
[tex]\[ z^2 + 10z - 24 = 0 \][/tex]
The general form of a quadratic equation is:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 10 \)[/tex], and [tex]\( c = -24 \)[/tex].
To find the solutions for [tex]\( z \)[/tex], we can use the quadratic formula:
[tex]\[ z = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
First, let's calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] into the discriminant:
[tex]\[ \Delta = 10^2 - 4(1)(-24) \][/tex]
[tex]\[ \Delta = 100 + 96 \][/tex]
[tex]\[ \Delta = 196 \][/tex]
Now we substitute the values back into the quadratic formula:
[tex]\[ z = \frac{{-10 \pm \sqrt{196}}}{2(1)} \][/tex]
Since [tex]\( \sqrt{196} = 14 \)[/tex], this becomes:
[tex]\[ z = \frac{{-10 \pm 14}}{2} \][/tex]
This gives us two solutions:
[tex]\[ z = \frac{{-10 + 14}}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ z = \frac{{-10 - 14}}{2} = \frac{-24}{2} = -12 \][/tex]
Therefore, one of the solutions to the quadratic equation [tex]\( z^2 + 10z - 24 = 0 \)[/tex] is:
[tex]\[ z = -12 \][/tex]
[tex]\[ z^2 + 10z - 24 = 0 \][/tex]
The general form of a quadratic equation is:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 10 \)[/tex], and [tex]\( c = -24 \)[/tex].
To find the solutions for [tex]\( z \)[/tex], we can use the quadratic formula:
[tex]\[ z = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
First, let's calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] into the discriminant:
[tex]\[ \Delta = 10^2 - 4(1)(-24) \][/tex]
[tex]\[ \Delta = 100 + 96 \][/tex]
[tex]\[ \Delta = 196 \][/tex]
Now we substitute the values back into the quadratic formula:
[tex]\[ z = \frac{{-10 \pm \sqrt{196}}}{2(1)} \][/tex]
Since [tex]\( \sqrt{196} = 14 \)[/tex], this becomes:
[tex]\[ z = \frac{{-10 \pm 14}}{2} \][/tex]
This gives us two solutions:
[tex]\[ z = \frac{{-10 + 14}}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ z = \frac{{-10 - 14}}{2} = \frac{-24}{2} = -12 \][/tex]
Therefore, one of the solutions to the quadratic equation [tex]\( z^2 + 10z - 24 = 0 \)[/tex] is:
[tex]\[ z = -12 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.